Association of angiopoietin‐1, angiopoietin‐2 and caspase‐5 polymorphisms with psoriasis vulgaris. (8th March 2015) - He, L.; Dang, L.; Zhou, J.; Bai, J.; Li, Y.‐Z.
Summary Background Psoriasis involves a multifaceted interplay of keratinocytes, blood vessels, immune system mediators and expressed genes. Aim To determine whether genetic polymorphisms in the angiopoietin‐1 (ANGPT1), angiopoietin‐2 (ANGPT2) and caspase‐5 (CASP5) genes are associated with an increased risk of developing psoriasis vulgaris (PV) in a Han population in northeastern China. Methods We analysed single nucleotide polymorphisms of ANGPT1 (rs2507800, rs1954727 and rs1010824), ANGPT2 (rs3739390, rs2442598 and rs1868554) and caspase‐5 (rs507879, rs518604 and rs523104) in 343 patients with PV and 347 healthy controls (HCs) by the SNaPshot method, and evaluated the risk for psoriasis conferred by the individual polymorphisms and haplotypes. Results The rs2442598 polymorphism of ANGPT2 was significantly associated with PV. The CT+TT genotype was present at an increased frequency in patients with PV (adjusted OR = 1.45, 95% CI 1.04–2.03, P = 0.03). However, the distribution of the other genotypes (rs2507800, rs1954727 and rs1010824 of ANGPT1; rs3739390 and rs1868554 of ANGPT2; and rs507879, rs518604 and rs523104 of caspase‐5) was not significantly different between patients with PV and the HCs. Furthermore, none of the genes in the haplotype‐based analysis showed any association with psoriasis risk. Conclusions Our data suggest that ANGPT2 variants may be involved in PV risk in a Han population in northeastern China.